Pengaruh Opini Auditor dan Pertumbuhan Penjualan Perusahaan pada Nilai Perusahaan - Diantari, Ketut Ita; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p10, 2019)
The study was conducted to identify and test empirically the influence of auditor opinion which is an external factor, and sales growth which is the company's internal factors on the firm’s value. The study was conducted on consumer goods industry sector companies for the period 2013-2017. Samples totaling 17 companies was selected purposively, so that 85 observations were obtained. The data analysis technique used is multiple linear regression. The results of the study show 1) the auditor's opinion does not affect the firm's value. 2) Company sales growth has a positive effect on firm’s value. Based on the results obtained, the research has theoretical implications, that is, it can support signal theory and become another research reference source related to firm’s value. The practical implication is to be considered by investors, creditors, and other interested parties in making business decisions. Keywords: auditor opinion, company sales growth, firm value